Mandibular metastasis of rectum adenocarcinoma: case report - Mehmet Ali Çetin; Süleyman Emre Karakurt; Ali Rıza Yamur; Hüseyin Dere (Gazi University, 2018)
Introduction: Mandibular metastases are quite rare and they constitute less than about %1 of the mandibular malignancies. In mandibular metastatic cases, patients' complaints generally include bony swelling with pain, tooth pain and tooth loss. Mandibular metastatic lesions mimic periodontal diseases; therefore careful examination is necessary. In differential diagnosis, osteosarcoma, which is a primary bone tumor, primary intraosseous squamous carcinoma, ameloblastoma, and temporomandibular joint diseases should be taken into consideration. Treatment modalities are surgery and chemoradiotherapy. Because of the poor prognosis, the goal of the treatment is only palliative. Case Report: A 51-year-old woman, operated due to rectal adenocarcinoma 3 years previously, was referred to our clinic with a complaint of swelling on the jaw. Cranial magnetic resonance imaging and maxillofacial computed tomography revealed a mass that extended to condyle and lead to bone destruction on the right ramus of the mandible. An incisional biopsy was performed. The histopathology was consistent with colorectal adenocarcinoma metastasis. The patient was referred to a medical oncologist. Conclusion: Differential diagnosis of mandibular lesions should be made carefully, and metastatic tumors should be kept in mind. In patients with history of lung cancer, breast cancer, colorectal carcinoma or similar tumors, oral findings such as tooth pain and tooth loss should be taken into consideration, as these may be the signs of head and neck metastases. Biopsy must be performed after radiological examination.